Prospect of Protected Agricultural Structure and its Constraints for Utilizing in Nepal - Shiva Kumar Jha; Jeet Chand; Sanjeet Kumar Jha; Bikash KC; Ganga Ram Bhandari; Mukti Nath Jha (Journal La Lifesci, 2022)
Protected agricultural structures have been adopted by commercial farmers throughout the world including Nepal to cope with climate change and its adverse effects on agriculture. Technology based production system is important for sustainable agricultural development. It could be the tool for low-income countries like Nepal where agriculture is the priority of income generation for the rural people. A field study was conducted in 2021 and 2022 to understand the prospects of protected agriculture structures adaptation by farmers and agricultural entrepreneur in Nepal. The study was traversed with both physical observation and the user’s interviews. The opportunities and the constraints have been critically analysed based on these field study along with the review of different policy documents and success stories published. This study found that the protected cultivation practice has been rapidly increased with increasing number of protected structures like plastic house or tunnel framed with bamboo or GI pipe, Agri-net house, naturally ventilated poly house and semi or hi-tech green house. In contrary, the import of horticulture products has also been increased more than 200% in last 10 years. This study finds the gap mismatching between technology enhancement, production and import of horticulture crops.